Characterizing the Developmental Trajectory of Sirolimus Clearance in Neonates and Infants. (8th August 2016) - Emoto, C; Fukuda, T; Mizuno, T; Schniedewind, B; Christians, Uwe; Adams, DM; Vinks, AA
Abstract : Sirolimus is increasingly being used in neonates and infants, but the mechanistic basis of age‐dependent changes in sirolimus disposition has not been fully addressed yet. In order to characterize the age‐dependent changes, serial sirolimus clearance (CL) estimates in individual young pediatric patients were collected and analyzed by population modeling analysis. In addition, sirolimus metabolite formation was also investigated to further substantiate the corresponding age‐dependent change in CYP3A activity. The increasing pattern over time of allometrically size‐normalized sirolimus CL estimates vs. age was well described by a sigmoidal Emax model. This age‐dependent increase was also observed within each individual patient over a 4‐year study period. CYP3A‐dependent sirolimus metabolite formation changed in a similar fashion. This study clearly demonstrates the rapid increase of sirolimus CL over time in neonates and infants, indicating the developmental change. This developmental pattern can be explained by a parallel increase in CYP3A metabolic activity.